2022
DOI: 10.3390/insects13111005
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Chloride Shows Effectiveness against the Poultry Red Mite (Dermanyssus gallinae)

Abstract: The poultry red mite (Dermanyssus gallinae) is the main pest of poultry, causing severe problems by being a vector of several animal and human pathogens. The number of miticides is few, and their efficacy in practice implies problems of residues and resistance; therefore, the demand for a new and safe agent is constant. The present publication investigated the effectiveness of lithium chloride under in vitro conditions on poultry red mites. This chemical currently appears to be one of the most promising altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Foods of animal origin are rich in naturally occurring micro-elemental lithium, such as milk, poultry meat and eggs (>7000 µg dry matter) [ 23 ]. As cereals constitute an important part in the poultry diet, and grains contain a low content of boron, 2 mg/kg of B are recommended for hens’ feed, even if B is not considered an essential micronutrient for fowls and other farm animals [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Foods of animal origin are rich in naturally occurring micro-elemental lithium, such as milk, poultry meat and eggs (>7000 µg dry matter) [ 23 ]. As cereals constitute an important part in the poultry diet, and grains contain a low content of boron, 2 mg/kg of B are recommended for hens’ feed, even if B is not considered an essential micronutrient for fowls and other farm animals [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lithium was also found to be effective for poultry red mite. Lithium concentrations of 5.52 M, 2.76 M, and 1.38 M were also tested on poultry red mite (Dermanyssus gallinae) recently [45]. The time needed for the death of 50% of the animals-i.e., reaching LD50-was 25, 45, and 134 min for the 5.52 M, the 2.76 M, and the 1.38 M concentrations, respectively, and similarly significant differences occurred for reaching the LD90 stage (64, 87, and 312.5 min for the 5.52 M, the 2.76 M, and the 1.38 M concentrations, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a feasible technological solution is already available should lithium become a widely authorised veterinary active substance in the near future [44]. Recently, it was revealed that lithium chloride also exerts effectivity on the poultry red mite [45]. To date, however, research on the acaricidal feature of the biometal has remained limited to its possible veterinary application.…”
Section: Introductionmentioning
confidence: 99%
“…Two separate tests were conducted to describe the dynamics of response and to determine the LC 50 values for the lithium chloride in dog ticks. In Test I, aqueous lithium chloride solutions (deionized water, LiCl a.r, Szkarabeusz Kft.,Pécs, Hungary) were used in the following concentrations: 5.520 M, 2.760 M, and 1.380 M, similar to those applied in previous studies on V. destructor and D. gallinae [ 8 , 10 ]. The dog ticks were immersed in 1 mL solutions in Eppendorf tubes (Thermo Fisher Scientific, Waltham, MA, USA) and slightly vortexed for 10 s to remove any air bubbles on the animals, ensuring an even contact exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Later, it was confirmed that its strong biocidal effect contributes to the high efficacy of the varroacide agent [ 8 ], and techniques relevant to beekeeping practice have been published for lithium-based Varroa control treatments [ 9 ]. Additionally, it has been recently revealed that lithium is effective against the poultry red mite in vitro [ 10 ].…”
Section: Introductionmentioning
confidence: 99%